Effects of lateral olfactory tract stimulation on Fos immunoreactivity in vasopressin neurones of the rat piriform cortex. (30th October 2017) - Tsuji, C.; Tsuji, T.; Allchorne, A.; Leng, G.; Ludwig, M.
Abstract : In the main olfactory system, odours are registered at the main olfactory epithelium and are then processed at the main olfactory bulb (MOB) and, subsequently, by the anterior olfactory nucleus (AON), the piriform cortex (PC) and the cortical amygdala. Previously, we reported populations of vasopressin neurones in different areas of the rat olfactory system, including the MOB, accessory olfactory bulb (AOB) and the AON and showed that these are involved in the coding of social odour information. Utilising immunohistochemistry and a transgenic rat in which an enhanced green fluorescent protein reporter gene is expressed in vasopressin neurones (eGFP‐vasopressin), we now show a population of vasopressin neurones in the PC. The vasopressin neurones are predominantly located in the layer II of the PC and the majority co‐express the excitatory transmitter glutamate. Furthermore, there is no sex difference in the number of neurones expressing vasopressin. Electrical stimulation of the lateral olfactory tract leads to a significant increase in the number of Fos‐positive nuclei in the PC, MOB, AOB, dorsal AON and supraoptic nucleus (SON). However, there was only a significant increase in Fos expression in vasopressin cells of the PC and SON. Thus, functionally distinct populations of vasopressin cells are implicated in olfactory processing at multiple stages of the olfactory pathway.